The Influence of Endothelial Nitric Oxide Synthase (eNOS) Genetic Polymorphisms on Cholesterol Blood Levels Among Type 2 Diabetic Patients on Atorvastatin Therapy - Abdullah, Sarah; Jarrar, Yazun; Alhawari, Hussam; Abed, Eyada; Zihlif, Malek (Endocrine, Metabolic & Immune Disorders-Drug Targets, 2021)
Background: Endothelial nitric oxide synthase (eNOS) plays a major role in the response of anti-hypercholesterol statin drugs. Genetic polymorphisms in the eNOS gene affect the activity of eNOS thereby modulating the statin response. Objective: This study investigated the influence of major functional eNOS gene polymorphisms (rs2070744, rs1799983, and rs61722009) on the lipid profile of type 2 diabetes mellitus (T2DM) Jordanian patients treated with atorvastatin. Methods: The sample comprised 103 T2DM patients who attended the diabetes clinic of Jordan University Hospital. The T2DM patients had regularly been taking 20 mg atorvastatin. The atorvastatin response was calculated by measuring the lipid profile before and after three months of atorvastatin treatment. The eNOS genotypes of the subjects were analyzed using polymerase chain reaction (PCR) followed by restriction fragment length polymorphism (RFLP) assay. Results: No significant association was found between eNOS genetic polymorphisms and the response to atorvastatin (ANOVA, p > 0.05). In addition, no significant difference in the frequency of eNOS genotypes was found between T2DM patients and healthy subjects. However, patients with eNOS rs1799983, 4a/4a, and rs61722009 G/G genotypes showed significantly lower levels of baseline total cholesterol (TC) and low density lipoprotein (LDL) than did patients carrying the rs1799983 4b/4b or rs61722009 T/T genotype (p < 0.05). The eNOS rs1799983 and rs61722009 polymorphisms were in complete linkage disequilibrium (D' = 1). Conclusion: Although no association was found between eNOS genetic polymorphisms and atorvastatin response, there was a significant association between the rs1799983 and rs61722009 genotypes and baselines levels of TC and LDL in Jordanian T2DM patients. These genetic variants affect cholesterol levels and may play a role in the susceptibility to cardiovascular diseases in T2DM patients. Further studies are needed to validate these findings.
Keywords: low density lipoprotein